Industrial Districts, Core Cities And Ownership Strategy Of Multinational Firms Investing In Italy - Stefano Elia; Lucia Piscitello; Sergio Mariotti (European Regional Science Association (ERSA), 2013)
This paper assesses the influence of spatial heterogeneity on the choice of entry modes by multinational enterprises (MNEs). We claim that the location of the target firm influences the choice of partial ownership, i.e., an MNE?s choice to maintain a local partner. MNEs normally execute partial acquisitions to reduce their liability of foreignness and to preserve their target?s inherent competencies, particularly in highly innovative and internationally competitive sectors. However, this phenomenon occurs less frequently if target firms are located in areas that are characterized by relevant externalities, such as core cities and industrial districts. In particular, core cities allow foreign MNEs to access not only a variety of information and knowledge, but also other externalities that are associated with international interconnectedness; industrial districts provide MNEs with easier access to industry-specific agglomeration economies (a local pool of skilled labor, local input-output linkages, and local knowledge spillovers). Thus, both types of locations reduce an MNE?s need to maintain a local partner, although these locations provide substitutes for different aspects of the target firm?s competences. Empirical evidence from foreign acquisitions of local manufacturing firms that occurred in Italy during the 2001-2010 period confirms these expectations.
Keywords: 330; local externalities; agglomeration economies; ownership choice; foreign acquisitions; multinational enterprises